Time-Varying Effects of Prasugrel Versus Clopidogrel on the Long-Term Risks of Stroke After Acute Coronary Syndromes: Results From the TRILOGY ACS Trial. Issue 4 (April 2016) - Chin, Chee Tang; Neely, Benjamin; Magnus Ohman, E.; Armstrong, Paul W.; Corbalán, Ramón; White, Harvey D.; Prabhakaran, Dorairaj; Winters, Kenneth J.; Fox, Keith A.A.; Roe, Matthew T.
Abstract : Background and Purpose—: The role of more intense, sustained platelet inhibition in preventing stroke after acute coronary syndrome (ACS) is unclear. We observed a signal for reduced stroke risk in the Targeted Platelet Inhibition to Clarify the Optimal Strategy to Medically Manage Acute Coronary Syndromes (TRILOGY ACS) trial after 12 months of treatment with prasugrel versus clopidogrel in medically managed patients with ACS. Methods—: We examined 7243 patients with ACS, aged <75 years and without prior stroke, analyzing differences in baseline characteristics between patients with and without a stroke event through 30 months with a Cox proportional hazards model. We also assessed the effect of prasugrel versus clopidogrel (plus aspirin) on risk of all stroke events and ischemic stroke over time with an extended Cox proportional hazards model. Results—: Stroke events were infrequent through 30 months (ischemic stroke=62; hemorrhagic stroke=15). Patients with stroke were older, had more comorbidities, and had a higher Global Registry of Acute Coronary Events (GRACE) risk score. There was a trend for a lower unadjusted frequency of all stroke events through 30 months for prasugrel versus clopidogrel: 31 (1.5%) versus 46 (2.2%); P =0.08. There was a significant treatment-by-time interaction for those with ischemic stroke ( P =0.03), consistent with the 12-month landmarked Kaplan–Meier log-rank test showing a reduced hazard of ischemic stroke after 12 months with prasugrel ( P =0.04). No significant interactions between treatment effect of prasugrel versus clopidogrel and time were observed for all stroke events. Conclusions—: We observed a potential late treatment effect for prasugrel versus clopidogrel for a reduced risk of ischemic stroke in medically managed patients with ACS aged <75 years. These hypothesis-generating findings suggest that longer duration and more potent platelet inhibition with prasugrel may be associated with lower risk of ischemic stroke after 12 months. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00699998.